VD_FINDINFO 4/2013/SNR vom 17. April 2013 - VD Tribunal cantonal (2013)
CONTRAT D'ENTREPRISE GÉNÉRALE, MANDAT, NORME SIA, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL | 363 CO, 398 al. 2 CO, 42 al. 2 CO, 97 CO